Bionomics and Control of Philosamia (Attacus) Cynthia Drury (Leptdoptera : Saturnitdae) - Misra, R. M.; Prasad, G.; Mishra, R. K.; Misra, B. M. (Indian Forester, 1991)
The deffotiation epidemic in ailanthus excelsa roxb in satyanarain research nursery was studies. The insect responsible for epidemic was philosamia cythia drury. This is a polyphagous pest and reported for the first time as deffolator of ailanthus excelsa Egg, larva, pups and adult of the species are described and notes on their biology are given. A fungal pathogen, beauveria basslana(Balsama) Vulliemin has been recorded killing the larvae of P.cynthia in the field. The pathogen appears to be a promising organism for microbial control of Ailanthus deffolator in the field.